2014
DOI: 10.1007/s10530-014-0744-8
|View full text |Cite
|
Sign up to set email alerts
|

The invasibility of small headwater streams by an emerging invader, Clarias gariepinus

Abstract: African sharptooth catfish Clarias gariepinus has been spread globally and is proven to be invasive with demonstrable impacts on a variety of biota in recipient ecosystems. There are concerns that this species will invade headwater stream communities that are already considered fragile and heavily impacted by non-native invasive fishes. There is however no information on the ability of C. gariepinus to penetrate or establish in these environments. This paper uses data collected over a seven year period from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…A study by Kadye and Booth () predicted that the probability of invasion by non‐native African sharptooth catfish Clarias gariepinus decreased from the mainstem Great Fish River to the headwater tributaries. This is in agreement with findings from Ellender, Woodford, and Weyl () who showed that although C. gariepinus did invade headwater tributaries, it was unlikely to become established and invasions were casual and originated from mainstem source populations.…”
Section: Literature Reviewsupporting
confidence: 93%
“…A study by Kadye and Booth () predicted that the probability of invasion by non‐native African sharptooth catfish Clarias gariepinus decreased from the mainstem Great Fish River to the headwater tributaries. This is in agreement with findings from Ellender, Woodford, and Weyl () who showed that although C. gariepinus did invade headwater tributaries, it was unlikely to become established and invasions were casual and originated from mainstem source populations.…”
Section: Literature Reviewsupporting
confidence: 93%
“…In both South Africa and Brazil, C. gariepinus appear to establish in mainstream and reservoir habitats from where they penetrate into tributary streams where they are contained only by natural (waterfalls) or man‐made (dams) barriers (Alves et al ., ; Vitule et al ., ; Ellender et al ., ). In the Sundays River for example, C. gariepinus were unable to establish in small irrigation ponds (Woodford et al ., ), but use the irrigation network to circumvent barriers and invade headwater stream environments (Ellender et al ., ). Although there is no evidence of establishment in South African headwater streams, the continued presence of C. gariepinus in these streams is facilitated by casual invasions from main stem source populations (Ellender et al ., ).…”
Section: Establishmentmentioning
confidence: 97%
“…In the Sundays River for example, C. gariepinus were unable to establish in small irrigation ponds (Woodford et al ., ), but use the irrigation network to circumvent barriers and invade headwater stream environments (Ellender et al ., ). Although there is no evidence of establishment in South African headwater streams, the continued presence of C. gariepinus in these streams is facilitated by casual invasions from main stem source populations (Ellender et al ., ).…”
Section: Establishmentmentioning
confidence: 97%
See 1 more Smart Citation
“…In headwater streams in South Africa’s Cape Floristic Region, an area of high freshwater fish and invertebrate biodiversity and endemism [ 22 ], the primary threat to aquatic biota in the region is considered to be predation by and competition with non-native fish species [ 6 , 23 ]. While non-native fish eradication using rotenone is currently considered the most appropriate conservation intervention [ 6 , 24 ], the public as well as the Department of Water Affairs (the South African regulatory authority) have expressed concern on the potential impact of river treatments on non-target organisms (see [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%